KUAT TEKAN DAN MODULUS ELASTIS BETON NORMAL YANG MENGGUNAKAN AGREGAT KASAR GABUNGAN - Samuel Layang; Petrisly Perkasa (Jurnal Teknik Sipil Unaya, 2022)
This study aims to obtain the percentage of coarse aggregate combined between crushed stone and uncrushed stone which produces the optimum compressive strength and elastic modulus of concrete. To achieve this goal, an experimental study was carried out in the laboratory using a cylindrical specimen with a diameter of 150 mm, a height of 300 mm with six variations of the mixture. Concrete mix planning is based on SNI 03-2834-2000 concerning Procedures for Making Normal Concrete Mixture Plans. The test results show that the greatest compressive strength and elastic modulus is produced by a concrete mixture in which all coarse aggregates use crushed stone with a compressive strength value of 10.12 MPa and an elastic modulus of 16413.57 MPa. For concrete mixtures that use a combination of the coarse aggregate of crushed stone and unbroken stone, the largest compressive strength and elastic modulus are produced from a mixture of 80% crushed stone and 20% uncrushed stone.